Underutilised crops drive socio-economic transformation in alternative food networks: a case study of diverse farm-to-table supply chains in Hungary - Alexandra Czeglédi (Agricultural and Food Economics)
Abstract This article explores the ways in which socio-economic transformations are unfolding within small-scale farm-to-table supply chains in the alternative food networks of Hungary, driven by underutilised crops (UCs) in the post-COVID-19 pandemic context. Through an in-depth ethnographic study, I explore how local landraces, cultivars and heirlooms are integrated into restaurant menus at accessible and mid-range prices. By collecting qualitative data from different supply chain actors, including small producers, a retailer, a distributor, chefs, restaurant owners, food bloggers and researchers, I identified four modus operandi of farm-to-table supply chains—indirect, direct, engaged and immediate types—through a classification based on different modes of multi-stakeholder collaboration. I present these four types by unpacking their actors' achievements, such as knowledge sharing, logistical collaboration, organisational restucturing, joint planning, and key challenges, such as trust building, quality, quantity and logistical gaps, and financial constraints. The aim of this article is twofold, to introduce an empirically-driven farm-to-table typolgy of alternative food networks and to provide insights into how underutilised crops contribute to socio-economic transformation, namely, towards a more horizontal and cooperative labour and organisational restructuring within small-scale farm-to-table supply chains in Hungary.